SOME CHARACTERISTICS OF PLIOCENE - QUATERNARY TECTONIC ACTIVITIES IN THE BACBO MARINE COASTAL ZONE BY ANALYSING AND SYTHESIZING SEISMIC DATA - Hung, Doan The; Tram, Le; Dai, Nguyen Ba (Vietnam Journal of Marine Science and Technology, 2006)
SOME CHARACTERISTICS OF PLIOCENE - QUATERNARY TECTONIC ACTIVITIES IN THE BACBO MARINE COASTAL ZONE BY ANALYSING AND SYTHESIZING SEISMIC DATA